ANALISIS PENGARUH DANA PIHAK KETIGA, NON PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO, CAPITAL ADEQUACY RATIO DAN INFLASI TERHADAP VOLUME PEMBIAYAAN MURABAHAH - Prisvina Anggraeni; Nurhayati Nurhayati (Universitas Muhammadiyah Semarang, 2021)
This study aims to determine the effect of Third Party Funds (DPK), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), CapitalAdequacy Ratio (CAR), and inflation simultaneously or partially on MurabahahFinancing Volume.The independent variables used in this study are Third Party Funds (DPK),Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), CapitalAdequacy Ratio (CAR), and Inflation. The population used in this study is IslamicCommercial Banks in Indonesia for the period 2015-2019. The sample used in thisstudy were 12 Islamic commercial banks, with a purposive sampling method so that52 research data were obtained. This study uses secondary data obtained from theannual reports of each bank. The data analysis method used is multiple linearregression analysis using SPSS 21.The results of this study indicate that partially the Third Party Fund (DPK)and the Financing to Deposit Ratio (FDR) have a positive and significant effect onMurabahah Financing Volume. Meanwhile, Non Performing Financing (NPF),Capital Adequacy Ratio (CAR), and inflation have no effect on MurabahahFinancing Volume. Then simultaneously Third Party Funds (DPK), NonPerforming Financing (NPF), Financing to Deposit Ratio (FDR), CapitalAdequacy Ratio (CAR), and Inflation have an effect on Murabahah FinancingVolume.